Organizational Lies In Schools - Yarım, Mehmet Ali (Bursa Teknik Üniversitesi, 2025)
The purpose of this research is to examine the causes and consequences of organizational lies in schools. The study is in the phenomenology model, which is one of the qualitative research methods. The study group of the research consists of administrators and teachers working in schools in the city center of Erzurum in the 2023-2024 academic year. In the interview, the data were obtained with a semi-structured interview form. The obtained data were analyzed by content analysis and descriptive analysis methods. According to the results of the research, organizational lies are at high levels in schools. Well-intentioned lies are often told in schools to motivate or help students. But in schools, malicious and harmful lies are told in order to put their colleagues in a difficult situation, to gain financial advantage, to obtain a position and position, and to cover up the crime. Lying in schools has individual consequences such as psychological distress, exclusion, self-deception, disrepute and rulelessness. According to the results of the research, there are organizational consequences of lying in schools such as dysfunction, inefficiency, negative climate and atmosphere, organizational insecurity, and decrease in organizational belonging. Lying in schools is very difficult to prevent, but detecting and taking action can bring significant benefits to leaders and administrators.

The purpose of this research is to examine the causes and consequences of organizational lies in schools. The study is in the phenomenology model, which is one of the qualitative research methods. The study group of the research consists of administrators and teachers working in schools in the city center of Erzurum in the 2023-2024 academic year. In the interview, the data were obtained with a semi-structured interview form. The obtained data were analyzed by content analysis and descriptive analysis methods. According to the results of the research, organizational lies are at high levels in schools. Well-intentioned lies are often told in schools to motivate or help students. But in schools, malicious and harmful lies are told in order to put their colleagues in a difficult situation, to gain financial advantage, to obtain a position and position, and to cover up the crime. Lying in schools has individual consequences such as psychological distress, exclusion, self-deception, disrepute and rulelessness. According to the results of the research, there are organizational consequences of lying in schools such as dysfunction, inefficiency, negative climate and atmosphere, organizational insecurity, and decrease in organizational belonging. Lying in schools is very difficult to prevent, but detecting and taking action can bring significant benefits to leaders and administrators.
Organizational Lies In Schools
Keywords: Educational Sociology; Eğitim Sosyolojisi